The Ability of Detecting Heart Rate Variability with the Photoplethysmography to Predict Major Adverse Cardiac Event in Acute Coronary Syndrome - Muhadi Muhadi; Sally A Nasution; Rudi Putranto; Kuntjoro Harimurti (Interna Publishing, 2016)
Aim: to assess heart rate variability (HRV) measurements using pulse photoplethysmograph (PPG) in predicting major adverse cardiac event (MACE) in acute coronary syndrome (ACS) patients. Methods: a prospective cohort study was conducted among hospitalized ACS patients. Heart rate variability as predictor was measured by PPG within 48 hours after admission and the incidence of MACE as outcome was identified during ICCU stay. The ability of HRV in predicting MACE during hospitalization was determined by area under ROC curve (AUC) of low frequency (LF), high fequency (HF), and LF/HF ratio parameters. Results: among 75 subjects included in the study, 14 (18.7%) were experienced MACE during hospitalization. HRV parameters of LF and LF/HF ratio have AUC of 0.697 (95% CI, 0.543-0.850) and 0.851 (0.741-0.962), respectively. Using cut-off point of 89.673 ms2, LF had PPV and NPV of 13% and 71%, respectively; while LF/HF ratio of 1.718 had PPV and NPV of 6% and 50%, respectively. Conclusion: the HRV parameters of LF and LF/HF ratio are moderate predictors for MACE and predict better ACS patients who will not develop MACE during hospitalization.